Exploring Ozone Precursor Patterns in The Urban Area: A Case Study in Peninsular Malaysia - Siti Hasliza Ahmad Rusmili,; Mohamad Hamzah, Firdaus; Mohd Saifullah Rusiman,; Lilis Sulistyorini,; Noorhelyna Razali, (International Journal of Integrated Engineering, 2025)
Ozone precursors are chemical compounds that interact with oxygen in the environment, leading to the formation of ozone. Volatile organic compounds (VOCs) are common ozone precursors. Ozone precursors can affect air quality and human health. The objective of this study is to investigate and evaluate ozone precursors in Cheras and Seremban in the central zone of Peninsular Malaysia using monthly data from 2018 to 2021. The Kolmogorov-Smirnov test found a p-value of less than 0.05, significantly rejecting the hypothesis of normal distribution. Exploratory data analysis was used to evaluate the data at both stations based on descriptive statistics, scatter plots, boxplots, and correlations between parameters. The maximum value of toluene from 2018 to 2021, is 5,738 ppb, which is more higher than Seremban's 2,228 ppb and than other ozone precursors in both stations. Meanwhile, the minimum of benzene, ethylbenzene and xylene in Cheras are   0.3201 ppb, 0.1470 ppb and 0.2910 ppb and in Seremban are 0.3794 ppb, 0.1770 ppb and 0.1400 ppb while the maximum value in Cheras are 1.3892 ppb, 0.7826 ppb and 1.3498 ppb and Seremban are 1.6955 ppb, 1.3117 ppb and 1.7801. Spearman's correlation shows that there is a strong positive monotonic relationship between toluene and benzene at both Cheras and Seremban stations (0.71 and 0.91) while most pollutants have a weak correlation with each other. After comparing the two locations, it was found that Cheras had a higher concentration of pollutants than Seremban. Cheras’ growing economy and central location mean that there are more manufacturers, fuel-burning vehicles, and chemicals emitting into the air than in Seremban. The results of the study can help governments develop more effective strategies to reduce the release of ozone precursors into the atmosphere, which can harm humans if emission limits are exceeded.